2002
DOI: 10.1086/340210
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy Using a Simian Virus 40–Derived Vector Inhibits the Development of In Vivo Human Immunodeficiency Virus Type 1 Infection of Severe Combined Immunodeficiency Mice Implanted with Human Fetal Thymic and Liver Tissue

Abstract: To evaluate the in vivo efficacy of gene therapy for treating human immunodeficiency virus type 1 (HIV-1) infection, a novel simian virus (SV) 40-derived vector gene delivery system that efficiently transduces human leukocytes was combined with a model using severe combined immunodeficiency mice infected with HIV-1 and implanted with human fetal thymic and liver tissue (thy/liv-SCID-hu mice). The SV40-derived vector, SV(Aw), which encodes a variable fragment antibody recognizing HIV-1 integrase (IN#33),was inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The use of intrabodies in other cell-based systems have not been reported to alter growth and development. [64][65][66] Although CCR5 intrabody expression is functional and limits the amount and duration of viral spread at the population level in CD4 + T cells isolated from the human thymus (Figure 3), additional studies are required to determine the variability of CAD-R5-mediated protection provided to individual CD4 + T cells derived from transduced CD34 + progenitors.…”
Section: Ccr5 Intrabody-mediated Protection and Enrichment Of T Cellsmentioning
confidence: 99%
“…The use of intrabodies in other cell-based systems have not been reported to alter growth and development. [64][65][66] Although CCR5 intrabody expression is functional and limits the amount and duration of viral spread at the population level in CD4 + T cells isolated from the human thymus (Figure 3), additional studies are required to determine the variability of CAD-R5-mediated protection provided to individual CD4 + T cells derived from transduced CD34 + progenitors.…”
Section: Ccr5 Intrabody-mediated Protection and Enrichment Of T Cellsmentioning
confidence: 99%
“…These vectors readily transduce neurons in vitro and in vivo, and have been effective in studying gene transfer as protection from HIV-1 in experimental systems. [37][38][39][40][41][42] We found that rSV40 gene delivery of transgenes SOD1 and GPx1, singly or in combination, significantly mitigated neuronal apoptosis mediated by gp120. The effectiveness and degree of protection of these vectors in delivering these antioxidant enzymes was also verified in vivo.…”
Section: Introductionmentioning
confidence: 75%
“…Our study indicates that a full-length Vp2 is not essential in a productive SV40 infection; it also suggests that the Vp2-unique coding region may be dispensable as long as the Vp3 reading frame and initiating AUG codon are maintained. -Herman et al, 1999;Goldstein et al, 2002). Chang & Wilson (1986) have suggested the packaging limit for SV40 to be between 284 and 460 extra base pairs.…”
mentioning
confidence: 99%